Evidence that a mitochondrial death spiral underlies antagonistic pleiotropy. Issue 3 (9th February 2017) - Stern, Michael
Summary: The antagonistic pleiotropy (AP) theory posits that aging occurs because alleles that are detrimental in older organisms are beneficial to growth early in life and thus are maintained in populations. Although genes of the insulin signaling pathway likely participate in AP, the insulin‐regulated cellular correlates of AP have not been identified. The mitochondrial quality control process called mitochondrial autophagy (mitophagy), which is inhibited by insulin signaling, might represent a cellular correlate of AP. In this view, rapidly growing cells are limited by ATP production; these cells thus actively inhibit mitophagy to maximize mitochondrial ATP production and compete successfully for scarce nutrients. This process maximizes early growth and reproduction, but by permitting the persistence of damaged mitochondria with mitochondrial DNA mutations, becomes detrimental in the longer term. I suggest that as mitochondrial ATP output drops, cells respond by further inhibiting mitophagy, leading to a further decrease in ATP output in a classic death spiral. I suggest that this increasing ATP deficit is communicated by progressive increases in mitochondrial ROS generation, which signals inhibition of mitophagy via ROS‐dependent activation of insulin signaling. This hypothesis clarifies a role for ROS in aging, explains why insulin signaling inhibits autophagy, and why cells become progressively more oxidized during aging with increased levels of insulin signaling and decreased levels of autophagy. I suggest that the mitochondrial death spiral is not an error in cell physiology but rather a rational approach to the problem of enabling successful growth and reproduction in a competitive world of scarce nutrients.